Egg consumption and growth in children: a meta-analysis of interventional trials - Larson, Elisabeth A.; Zhao, Zaixin; Bader-Larsen, Karlen S.; Magkos, Faidon (Frontiers in Nutrition, 2024)
Introduction: Stunting and wasting are prevalent in low-and middle-income countries, putting children at risk for disease and disability. Eggs are a nutrient-rich food that can potentially facilitate growth. Purpose: The aim of this meta-analysis was to evaluate the potential beneficial effect of egg supplementation on growth in children. Methods: Following the PRISMA guidelines, PubMed and Healthline (Ovid) were systematically searched for interventional studies on egg supplementation for growth in children aged 6 months to 18 years, with no restrictions on date. Studies were evaluated for quality using Cochrane's GRADE technique. Data were pooled and reported as means and 95% confidence intervals.Results: Seven studies reporting on 9 unique interventions in 3575 male and female participants were included in the meta-analysis. Participants in the intervention groups experienced significantly greater increases in height/length (by 0.47 [0.13, 0.80] cm, p < 0.01) and weight (by 0.07 [0.01, 0.13] kg, p = 0.03) when compared to those in the control groups. Conclusion: Eggs are an affordable, nutritious option for improving growth in children, though more studies with longer interventions are warranted.